1996
DOI: 10.1016/s0006-3495(96)79563-2
|View full text |Cite
|
Sign up to set email alerts
|

Use-dependent inhibition of Na+ currents by benzocaine homologs

Abstract: Most local anesthetics (LAs) elicit use-dependent inhibition of Na+ currents when excitable membranes are stimulated repetitively. One exception to this rule is benzocaine, a neutral LA that fails to produce appreciable use-dependent inhibition. In this study, we have examined the use-dependent phenomenon of three benzocaine homologs: ethyl 4-diethylaminobenzoate, ethyl 4-ethoxybenzoate, and ethyl 4-hydroxybenzoate. Ethyl 4-hydroxybenzoate at 1 mM, like benzocaine, elicited little use-dependent inhibition of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
(31 reference statements)
3
28
0
1
Order By: Relevance
“…Consistent with earlier studies, we found almost no use-dependent inhibition by benzocaine 20,25,33,39 ( Supplementary Fig. S5), suggesting that a protonated amine is necessary for use-dependent inhibition.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with earlier studies, we found almost no use-dependent inhibition by benzocaine 20,25,33,39 ( Supplementary Fig. S5), suggesting that a protonated amine is necessary for use-dependent inhibition.…”
Section: Resultssupporting
confidence: 92%
“…Rapid recovery from inactivation explains the lack of use-dependent block at stimulating frequencies below 50 Hz. Lack of use-dependent block has equally been described for the structurally related local anaesthetic benzocaine (Quan et al, 1996). In contrast, lidocaine induces substantial use-dependent block, even at lower stimulating frequencies than those used in our experiments (Fan et al, 1996).…”
supporting
confidence: 71%
“…In contrast, lidocaine induces substantial use-dependent block, even at lower stimulating frequencies than those used in our experiments (Fan et al, 1996). Structure ± activity studies of dierent local anaesthetics and their derivatives have shown that the rate of dissociation from inactivated channels, which determines the accumulation of frequency-dependent block during repetitive stimulation, is related primarily to the size of the aliphatic side-chains (Quan et al, 1996), the molecular weight, and charge (Ehring et al, 1988). Thus, the lack of use-dependent block seen with all the phenol derivatives we have studied compared with lidocaine could be attributed to dierences in molecular weight.…”
mentioning
confidence: 71%
“…The results on the kinetics of recovery from inactivated channel block explain the lack of use-dependent block at stimulating frequencies lower than 50 Hz seen with most phenolic compounds at concentrati ons below the IC 50 for rest block. Lack of use-dependent blockade has equally been described for the structurally related local anaesthetic benzocaine [63]. In contrast, lidocaine induces substantial use-dependent block, even at lower stimulating frequencies [18].…”
mentioning
confidence: 93%
“…In contrast, lidocaine induces substantial use-dependent block, even at lower stimulating frequencies [18]. Structure-activity studies of different local anaesthetics and their derivatives have shown that the rate of dissociation from inactivated channels, which determines the accumulation of frequency-dependent block during repetitive stimulation, is related primarily to the size of the aliphatic side-chai ns [63], the molecular weight, and charge [2]. Thus, the lack of frequencydependent block seen with compounds with single substituents at the phenol ring compared with lidocaine could be attributed to differences in molecular weight.…”
mentioning
confidence: 99%